Analisis Pengaruh Manajemen Risiko Keuangan Pada UMKM Story Ceta Kabupaten Cianjur Terhadap Daya Saing Usaha - Salsa Dwi Putri; Deri Apriadi (Jurnal Publikasi Ekonomi dan Akuntansi, 2025)
This study analyzes the effect of financial risk management on the competitiveness of MSME Story Ceta in Cianjur Regency, which is engaged in plant-based food with the main products of birthday cakes, dessert boxes, baked sponge cakes, and vegetable flour. Using a qualitative method with a case study approach, data was collected through interviews, observations, and literature studies. The results show that financial risk management, such as adaptive cash flow management, consistent financial recording, supplier diversification, and utilization of social capital, significantly improves the financial stability and competitiveness of MSMEs. Financial literacy is an important supporting factor in the effectiveness of risk management. However, MSMEs face constraints in the form of limited access to formal financing and low financial literacy. This study makes theoretical and practical contributions by emphasizing the importance of integrating financial risk management and financial literacy to improve the competitiveness of MSMEs. The practical implications can be used to develop training programs and policies to support MSMEs at the local level.